Secondary Maxillary and Orbital Floor Reconstruction With a Free Scapular Flap Using Cutting and Fixation Guides Created by Computer-Aided Design/Computer-Aided Manufacturing. Issue 8 (November 2017) - Morita, Daiki; Numajiri, Toshiaki; Tsujiko, Shoko; Nakamura, Hiroko; Yamochi, Ryo; Sowa, Yoshihiro; Yasuda, Makoto; Hirano, Shigeru
Abstract : Abstract: Computer-aided design/computer-aided manufacturing (CAD/CAM) guides are now widely used in maxillofacial reconstruction. However, there are few reports of CAD/CAM guides being used for scapular flaps. The authors performed the secondary maxillary and orbital floor reconstruction using a free latissimus dorsi muscle, cutaneous tissue, and scapular flap designed using CAD/CAM techniques in a 72-year-old man who had undergone partial maxillectomy four years previously. The patient had diplopia, the vertical dystopia of eye position, and a large oral-nasal-cutaneous fistula. After the operation, the authors confirmed that the deviation between the postoperative and preoperative planning three-dimensional images was less than 2 mm. Because scapular guides require 3 cutting surfaces, the shape of the scapular guide is more complex than that of a conventional fibular guide. In orbital floor reconstruction, the use of a CAM technique such as that used to manufacture the authors' fixation guide is as necessary for accurate, safe, and easy reconstruction as is preoperative CAD planning. The production of a fixation guide as well as a cutting guide is particularly useful because it is difficult to determine the angle for reconstructing the orbital floor by freehand techniques. In this case, the orbital floor was reconstructed based on a mirror image of the healthy side to avoid overcompression of the orbital tissue. Although the patient's vertical dystopia of eye position was improved, diplopia was not improved because, for greater safety, the authors did not plan overcorrection of the orbital volume.